Geno/cytotoxicty and Apoptotic Properties of Phenolic Compounds from the Seeds of Dorema Glabrum Fisch. C.A - Morteza Eskandani; Elmira Dadizadeh; Hamed Hamishehkar; Hossein Nazemiyeh; Jaleh Barar (BioImpacts, 2014)
Introduction: Dorema glabrum (Apiaceae) is a rare and monocarpic species distributed in Transcaucasia and North West of Iran. We aimed to explore anticancer potency of bioactive compounds from the seeds of Dorma glabrum. Methods: Methanol extract was subjected to phytochemical investigation using normal phase Sep-pak and reversed-phase HPLC, and cytotoxic effect of isolated compounds on CAOV-4 cell line was evaluated. Furthermore, Annexin V/PI staining and comet assay were used to study genotoxicity of compounds. Results: Diglucosyl caffeoyl ester (1), Glucopyranosylcaffeic acid (2) and skimmin (3), were identified. MTT cytotoxicity assay showed growth inhibition of CAOV-4 cells due to treatment with compunds (1), (2) and (3) with an IC50 of 99.7, 87.3 and 70.03 µg/ml at 48 h, respectively. Annexin V-FITC/PI staining showed occurrence of early/late apoptosis in the (1)-treated cells, while (2)-and (3)-treated cells necrosis/late apoptosis was dominant event. Single/double strands DNA breakages were observed by comet assay in all treatments. Conclusion: This work provides sufficient information about anti-cancer properties of the diglucosyl caffeoyl ester from the seeds of D. glabrum.